Contact allergy to common ingredients in hair dyes. (19th June 2013) - Søsted, Heidi; Rustemeyer, Thomas; Gonçalo, Margarida; Bruze, Magnus; Goossens, An; Giménez‐Arnau, Ana M.; Le Coz, Christophe J.; White, Ian R.; Diepgen, Thomas L.; Andersen, Klaus E.; Agner, Tove; Maibach, Howard; et al.
Abstract Background p‐Phenylenediamine (PPD) is the primary patch test screening agent for hair dye contact allergy, and approximately 100 different hair dye chemicals are allowed. Objectives To examine whether PPD is an optimal screening agent for diagnosing hair dye allergy or whether other clinically important sensitizers exist. Methods Two thousand nine hundred and thirty‐nine consecutive patients in 12 dermatology clinics were patch tested with five hair dyes available from patch test suppliers. Furthermore, 22 frequently used hair dye ingredients not available from patch test suppliers were tested in subgroups of ∼ 500 patients each. Results A positive reaction to PPD was found in 4.5% of patients, and 2.8% reacted to toluene‐2, 5‐diamine (PTD), 1.8% to p‐aminophenol, 1% to m‐aminophenol, and 0.1% to resorcinol; all together, 5.3% (n = 156). Dying hair was the most frequently reported cause of the allergy (55.4%); so‐called 'temporary henna' tattoos were the cause in 8.5% of the cases. p‐Methylaminophenol gave a reaction in 20 patients (2.2%), 3 of them with clinical relevance, and no co‐reaction with the above five well‐known hair dyes. Conclusions Hair dyes are the prime cause of PPD allergy. PPD identifies the majority of positive reactions to PTD, p‐aminophenol and m‐aminophenol, but not all, which justifies additional testing with hair dye ingredients from the used product.